2008
DOI: 10.1002/j.1551-8833.2008.tb08131.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Changes in Water Quality Data

Abstract: Timely deployment of contaminant warning systems requires on‐line sensors and advancement of data analysis and decision support systems to accurately detect water quality changes. As a demonstration of event detection in water quality data, three water quality change‐detection algorithms were developed and used to detect changes in water quality observed at four locations within a distribution system. Each data set was “spiked” with simulated anomalous water quality values of 1 h duration and 10 levels of spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…As summarized by McKenna et al [10], two types of approaches to developing and testing event detection using water quality signals have been examined. First, laboratory and test-loop evaluation of sensors and associated event detection algorithms provides direct measurement of chemical changes in background water quality caused by specific contaminants [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized by McKenna et al [10], two types of approaches to developing and testing event detection using water quality signals have been examined. First, laboratory and test-loop evaluation of sensors and associated event detection algorithms provides direct measurement of chemical changes in background water quality caused by specific contaminants [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The second approach to event detection is based on signal processing and data driven techniques [10,[15][16][17][18][19][20]. For example, Hart et al [15] reported a linear prediction filter (LPF).…”
Section: Introductionmentioning
confidence: 99%
“…In the CANARY event detection tool [10] provided by the US EPA, detection techniques based on linear filters [20] and multivariate distance metrics [15] have been implemented, as well as sensor fusion techniques to take into account the spatial distribution of water quality sensor measurements [16].…”
Section: Contamination Detection Methodologiesmentioning
confidence: 99%
“…On the one hand, the Time Series Models (TSM) capture the temporal redundancy. In particular, we consider in this work the HoltWinters method (Winters, 1960), the Multivariate Differences algorithm (MV) (Mckenna et al, 2008) and an Artificial Neural Network (ANN) trained with historical data to forecast observations (Palani et al, 2008).…”
Section: Data Pipelinementioning
confidence: 99%
“…The Multivariate Distance algorithm (Mckenna et al, 2008) allows to detect changes in a group of parameters. In this work, the group of parameters are the observed by each multi-parameter device.…”
Section: Time Series Modelsmentioning
confidence: 99%